2008
DOI: 10.1111/j.1537-2995.2008.01790.x
|View full text |Cite
|
Sign up to set email alerts
|

Erythrocyte‐magnetized technology: an original and innovative method for blood group serology

Abstract: EMT is tailored to meet the needs of the transfusion service and represents an important advance in the field of immunohematology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 13 publications
3
24
0
Order By: Relevance
“…Discrepancies were usually a result of weak reactions in manual testing; both studies indicated that this device is more sensitive in detecting agglutination reactions. The QWALYS system utilizes erythrocyte-magnetized technology [25], and its performance in ABO blood typing has been reviewed by many researchers. The QWALYS-2 device was examined by Schoenfeld et al [26], who concluded that it was suitable for ABO grouping.…”
Section: Discussionmentioning
confidence: 99%
“…Discrepancies were usually a result of weak reactions in manual testing; both studies indicated that this device is more sensitive in detecting agglutination reactions. The QWALYS system utilizes erythrocyte-magnetized technology [25], and its performance in ABO blood typing has been reviewed by many researchers. The QWALYS-2 device was examined by Schoenfeld et al [26], who concluded that it was suitable for ABO grouping.…”
Section: Discussionmentioning
confidence: 99%
“…[12] The introduction of newer techniques such as column agglutination technique (CAT), Solid Phase Red Cell Adherence Assay (SPRCA), and erythrocyte-magnetized technique (EMT) have tried to overcome these short comings and bring about an improvement in the quality of testing and the reproducibility of results. [1–3] These new technologies are amenable to automation and major manufacturers in this field have come up with user-friendly semi-automated and fully automated equipments for immunohematology tests with varying throughputs depending upon the work load of a blood bank. We, here, present a brief introduction of major equipments available and the requirements for shifting from the conventional technology to the automated systems.…”
Section: Introductionmentioning
confidence: 99%
“…In the available studies, it has been shown a performance comparable with that of gel CAT. [3] A comparison of the newer technologies with the conventional tube testing has been compiled in Table 1. [178101415] The newer methods have added to the quality of testing but none of the methods has been found to be unequivocally superior to others.…”
Section: Introductionmentioning
confidence: 99%
“…The principles of EMT were described previously 1,2 . The EMT is based on the adsorption of paramagnetic compounds on the membrane of the RBCs.…”
Section: Methodsmentioning
confidence: 99%
“…The principle of EMT is based on magnetization of red blood cells (RBCs) and avoids centrifugation and washing steps. This new method was recently described in detail 2 …”
mentioning
confidence: 99%